An ethical assessment of low carbon vehicles using cost benefit analysis. (2016) - Thomopoulos, Nikolas; Harrison, Gillian
Global concerns about climate change, as confirmed at COP21, have led to lower carbon emissions environmental policies, particularly in the road transport sector. Through an empirical analysis of low carbon vehicle (LCV) policies in California, this paper contrasts the findings from diverse distribution theories between income quintiles - used as a proxy for societal groups - to address vertical equity concerns and offer an overview of impact distribution to policy makers. Thus, it contributes in operationalising ethical theories within transport cost benefit analysis and revisiting impact distribution when promoting low carbon vehicles. Findings indicate that manufacturer penalties are the most effective policy measure to avoid cost transfer between stakeholders. Yet, the analysis shows that those purchasing small LCVs may face disproportional vehicle purchase cost increases which needs to be considered by policy makers. Thus, this paper makes a methodological contribution regarding CBA in practice as well as providing policy relevant recommendations.